The hero's guide to saving your kingdom - Healy, Christopher, 1972-; Harris, Todd (New York : Walden Pond Press, 2012)
"The four princes erroneously dubbed Prince Charming and rudely marginalized in their respective fairy tales form an unlikely team when a witch threatens the whole kingdom" --Provided by publisher.
Keywords: Fairy tales; Princes -- Juvenile fiction; Witches -- Juvenile fiction; Humorous stories; Fantasy fiction